Meningkatkan Hasil Belajar PKn tentang Lembaga Pemerintahan Desa - Riswanto Riswanto (Academy of Education Journal, 2018)
One of the goals of national education is to educate the life of the nation, but efforts to realize the goals of education are not easy. In fact, there are many obstacles faced by both students and teachers. The level of mastery of learning material in SD Lumbir State Lumbir UPK is not in accordance with the criteria of success. Therefore teachers need to make improvements to learning through Classroom Action Research (CAR). Classroom Action Research begins with self-reflection, discussing with colleagues (collaborating), knowing the problems faced and finding alternative solutions that consist of planning, implementing, observing and reflecting in each cycle. In this study the teacher uses the field trip method which will be divided into three cycles, each cycle consisting of two meetings. The purpose of this study is to improve student learning outcomes.After conducting research through 3 cycles with Minimum Completion Criteria (KKM) 7.5, the results obtained increased each cycle from the initial study to only 3 children who completed learning or 18%, the first cycle of 6 children who completed learning or 37%, cycle II as many as 10 children completed study or 62% and cycle III 14 students completed study or 87% of the total grade IV students were 17 students. So, the use of field trip methods has succeeded in increasing student activity and learning outcomes. After carrying out this research teachers should be able to use appropriate methods and can improve student learning outcomes so that learning is successful and effective.